Combined Transcriptome and Proteome Analysis to Elucidate Salt Tolerance Strategies of the Halophyte Panicum antidotale Retz - Hussain, Tabassum; Asrar, Hina; Zhang, Wensheng; Gul, Bilquees; Liu, Xiaojing (Frontiers in Plant Science, 2021)
Panicum antidotale, a C4 monocot, has potential to reclaim saline and dry lands and to be utilized ‎as fodder / forage. Its adaptability to survive saline stress has been proven with eco-physiological ‎and biochemical studies. However, little is known about the its molecular mechanisms of salt ‎tolerance. Here, an integrated transcriptome and proteome analysis approach, based on RNA ‎sequencing and LC-MS/MS, was used to identify the said mechanisms. Plants were treated with ‎control (0 mM), low (100 mM) and high (300 mM) NaCl treatments to distinguish beneficial and ‎toxic pathways influencing plant biomass. Results indicated differential expression of 3179 (1126 ‎up-regulated/2053 down-regulated) and 2172 (898 up-regulated/1274 down-regulated) genes ‎‎(DEGs), and 514 (269 up-regulated/245 down-regulated) and 836 (494 up-regulated/392 down-‎regulated) proteins (DEPs) at 100 and 300 mM NaCl, respectively. Among these,large most of ‎proportion of up-regulatedupregulated genes genes and proteins wereas involved in salt resistance ‎strategies such as proline biosynthesis, the antioxidant defense system, ions homeostasis, and sugar ‎accumulation at low salinity level. On the other hand, the expression of several genes and proteins ‎involved in respiratory process werewere down-regulateddownregulated, indicating the inability of ‎plants to meet their energy demands at high salinity levels. Moreover, the impairments in ‎photosynthesis were also evident with the reduced expression of genes regulating structure of ‎photosystems and increased expression of abscisic acid (ABA) mediated pathways which limits ‎stomatal gas exchange. Similarly, the disturbance in fatty acid metabolism and activation of ‎essential ion transport blockers damaged the integrity of the cell membrane, which was also evident ‎with increasedenhanced malondialdehyde (MDA). Overall, Aanalysis of pathways revealed plant ‎optimal performance at low salinity was related to enhanced metabolism, antioxidative defense, cell ‎growth and signaling pathways, whereas high salinity inhibited biomass accumulation by altered ‎expression of numerous genes involved in photosynthesiscarbon metabolism, signaling, ‎transcription, and translation. The data provide the first global analysis of the mechanisms ‎imparting salt stress tolerance of any halophyte at transcriptome and proteome levels. and allow us ‎to contrast benchmark mechanisms in related non-halophytes. ‎